A study of predation behavior of Macrocyclops albidus (Jurine) on Culex quinquefasciatus larvae - Bassat, S.F.; Ghanim, F.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted to investigate the predation behavior of crustacean zooplankton M. albidus for first instar mosquito larvae of Culex quinquefasciatus, which may be represented as an indicator of the species activity for biological control of mosquito larvae. Results revealed that females spend 6.30 min. as average to find the mosquito larval and to catch it, whereas it consumed 7.20 min. in digestion of the prey. On the other hand the corresponding means for male were 10.29 and 4.00 min. respectively. Differences between females and males were not significant for the time consumed to catch the prey whereas the differences were significant (P < 0.05) in regard to the time consumed to digest the prey. Results also revealed that the mean total time (catch and digest time) of females and males were 13.55 and 14.29 min. respectively and the differences between them were not significant.